The Prevalence Rate and Anatomic Location of Colorectal Adenoma and Cancer Detected by Colonoscopy in Average-Risk Individuals Aged 40-80 Years - Strul, Hana; Kariv, Revital; Leshno, Moshe; Halak, Aharon; Jakubowicz, Markus; Santo, Moshe; Umansky, Mark; Shirin, Haim; Degani, Ya'ara; Revivo, Miri; Halpern, Zamir; Arber, Nadir (The American journal of gastroenterology, 2006)
The role of screening colonoscopy for colorectal (CR) neoplasia in average-risk population, remains to be determined. To evaluate the prevalence and anatomic location of CR adenoma and carcinoma and the morbidity of colonoscopy in individuals at average risk for CR cancer (CRC). A retrospective prevalence study of subjects aged 40-80 yr, with no cancer-related symptoms, personal or family history of CR neoplasia, who underwent a colonoscopy. Enrolled were 1,177 persons; 183 aged 40-49 yr (young), 917 aged 50-75 yr, and 77 aged 76-80 yr (elderly). The prevalence of overall CR neoplasia, advanced neoplasia, and cancer was 20.9%, 6.3%, and 1.1%, respectively. In the 50-75 age group, the prevalence of overall adenoma, advanced neoplasia, and cancer was 21.3%, 6.7%, and 1.2%, respectively. Of the 206 neoplasia cases, 21-43% harbored proximal neoplasia beyond the reach of sigmoidoscopy, without distal lesions. Among the elderly, the prevalence of overall adenoma, advanced neoplasia, and cancer reached 26.0%, 14.3%, and 2.6%, respectively. In the young group, 9.8% had overall neoplasia, 1.1% had advanced adenoma, and none had CRC. Procedure-related morbidity rate was 0.1%, with no perforations, bleedings, or mortality. Screening colonoscopy in average-risk subjects demonstrated a considerable prevalence of CR neoplasia and proximal lesions beyond the reach of sigmoidoscopy. The morbidity rate was negligible. Primary screening colonoscopy should be considered in health programs for the average-risk population, beginning at the age of 50 yr. The significantly high rate of advanced and proximal neoplasia in the elderly, encourages the inclusion of healthy subjects aged 76-80 yr in future prospective studies.